Assessment of Medicalization of Pregnancy and Childbirth in Low-risk Pregnancies: A Cross-sectional Study - Shadi Sabetghadam; Afsaneh Keramat; Shahrbanoo Goli; Mina Malary; Sedighe Rezaei Chamani (Shiraz University of Medical Sciences, 2022)
Background: Medicalization may lead to over-testing during pregnancy and increased cesarean section (CS). This study investigated the medicalization of low-risk pregnancies and childbirths in Rasht, Iran. Methods: In this cross-sectional study, 337 postpartum women completed a demographic questionnaire and the Medicalized Pregnancy and Childbirth checklist. In this study, medicalization indicators were the source of providing prenatal care, prenatal screening for aneuploidy, number of received care, hospitalization before the onset of labor, intrapartum drug use, and CS. Demographic data were reported using descriptive statistics. Chi-square or Fisher's exact and Man-Whitney tests were used for comparison purposes. Logistic regression was run to determine the medicalization indicators associated with the mode of childbirth. Results: Of the participants, 82.2% received prenatal care from obstetricians, 85.8% had undergone prenatal screening tests. There was a significant difference between the median number of ultrasound examinations (P=0.006), prenatal screening for aneuploidy (P=0.002), and multivitamin/mineral supplements use (p <0.001), according to the source of providing prenatal care. Of the participants, 67.1% had CS. Women who received prenatal care from obstetricians had about 2.3 times more odds of CS (OR=2.23, P=0.019). Furthermore, with the increased number of ultrasounds, the odds of CS augmented by 25% (OR=1.25, P=0.013). Finally, 26.4% of the participants were hospitalized before the onset of labor; the intervention increased the odds of CS more than twice (OR=2.08, P=0.026). Conclusion: The study showed a picture of medicalization in low-risk pregnancies.Of the medicalization indicators, the source of providing prenatal care, time of admission, and use of ultrasounds were associated with CS. Midwife-led care could diminish medicalization.